On demand cleaning service recommendation tool - Liu, Jie Wei (2020)
Nowadays, the mobile application are getting more important and popular for the people. This technology is also getting more advance time by time. Mobile application is usually used to produce users with related services to those penetrated on PCs. On the other hand, the recommender system also getting popular and widely used in many application and website. Recommender system is usually used to predict the eventual choice of a set items for a user, and suggest it to users. In this modern era with a large number of info, it is needed for a system that provide recommendation features to suggest the items to users. In this paper, it is mainly about the recommender system and mobile application for users to call for the janitorial service and recommend user some suitable plans. In order to achieve this goal, a score-based recommendation method will be implemented. Firstly, the system would process the input parameter such as budget and time that entered by the users to calculate the value of preferences with package. After that, the system will calculate the weight for preferences based on the important level entered by user. After that, the system will calculate the score for each package and display the package with higher score as recommendation result to the users.